Reasons for drug administration problems and perceived needs for assistance of patients, family caregivers, and nurses: a qualitative study - Lampert, Anette; Haefeli, Walter E.; Seidling, Hanna (Journal of patient safety, 2020)
Objective: Investigation of drug administration problems, respective causes, and needs for assistance. - Methods: Focus group discussions with patients, family caregivers, and nurses were conducted using a semi-structured interview guideline for a focused exploration of the participants’ drug administration experiences and perceived needs for assistance. All discussions were audio-recorded and video-recorded, verbatim transcribed, and analyzed according to Mayring’s qualitative content analysis. - Results: In total, 6 focus group discussions were conducted. The qualitative content analysis revealed that patients and family caregivers frequently trivialized drug administration, were unaware of errors, and primarily blamed the dosage form of causing administration problems. Nurses also considered health-care system-related conditions and patient factors as potential causes of administration problems. - Conclusions. The administration problems and perceived causes were multifaceted and often directed toward inappropriate dosage forms or health-care system-related conditions rather than critically questioning the medicine user’s administration skills. To increase medicine users’ motivation to scrutinize wrong administration practices, health-care professionals should consider individual perspectives on administration problems and perceived causes, assist medicine users’ to identify the true cause of a distinct problem, and provide individualized support.
Gesehen am 06.08.2020